Prostorsko planiranje za potrebe obrambe - Zavodnik Lamovšek, Alma (Geodetski vestnik, 2001)
Nowadays, spatial planning - especially its contents and methodology - is very close related to the geographical information system (GIS). In the paper the relationship of spatial planning for the purpose of defense of Republic of Slovenia and GIS is presented. Some possibilities for further development of the use of GIS in the procedures of spatial planning to the emphasis on defense are discussed
Keywords: GIS; obramba; prostorsko planiranje; spatial planning